2021
DOI: 10.1002/kjm2.12406
|View full text |Cite
|
Sign up to set email alerts
|

The association between oral health status and the clinical outcome of cirrhotic patients on the waiting list for liver transplantation

Abstract: Liver transplantation (LT) candidates often present with poor oral hygiene, which could potentially lead to systemic infections and sepsis owing to their cirrhotic state.In this study, we investigated the oral health status of LT candidates and propose guidance for the detection and treatment of encountered oral lesions among these patients. The decayed, missing, and filled teeth (DMFT) index was determined through oral examination. The presence of dental calculus was detected using panoramic radiography and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 36 publications
0
3
0
6
Order By: Relevance
“…Entre os 19 estudos incluídos, 11 avaliaram apenas portadores de cirrose hepática avançada e candidatos a transplante de fígado (Kwak et al, 2020), (Zahed, Ranjbar, et al, 2020), (Grønkjaer et al, 2018), (Lins et al, 2017), (Wu et al, 2021), (Hicks, 2015), (Helenius-Hietala et al, 2012), (Grønkjaer et al, 2021), (Lins et al, 2011), (Pidhorodeckyj et al, 2018), (Ramaglia et al, 2019), seis avaliaram grupo pré transplante e controles sadios (Zahed, Bahador, et al, 2020), (di Profio et al, 2018, (Ghapanchi et al, 2019), (Ghapanchi et al, 2020), (Sérgio et al, 2012, (Castellanos-Cosano et al, 2013), um estudo avaliou participantes no pré e pós transplante em comparação com grupo controle saudável (Schmalz et al, 2018), outro comparou pacientes do prétransplante com os do pós-transplante (Kauffels et al, 2017).…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Entre os 19 estudos incluídos, 11 avaliaram apenas portadores de cirrose hepática avançada e candidatos a transplante de fígado (Kwak et al, 2020), (Zahed, Ranjbar, et al, 2020), (Grønkjaer et al, 2018), (Lins et al, 2017), (Wu et al, 2021), (Hicks, 2015), (Helenius-Hietala et al, 2012), (Grønkjaer et al, 2021), (Lins et al, 2011), (Pidhorodeckyj et al, 2018), (Ramaglia et al, 2019), seis avaliaram grupo pré transplante e controles sadios (Zahed, Bahador, et al, 2020), (di Profio et al, 2018, (Ghapanchi et al, 2019), (Ghapanchi et al, 2020), (Sérgio et al, 2012, (Castellanos-Cosano et al, 2013), um estudo avaliou participantes no pré e pós transplante em comparação com grupo controle saudável (Schmalz et al, 2018), outro comparou pacientes do prétransplante com os do pós-transplante (Kauffels et al, 2017).…”
Section: Resultsunclassified
“…Vários estudos incluídos desta revisão mostraram que a saúde bucal de pacientes com cirrose avançada e indicação ao transplante não é satisfatória (Kwak et al, 2020), (Grønkjaer et al, 2018), (Lins et al, 2017), (Ghapanchi et al, 2019), (Wu et al, 2021), (Hicks, 2015), (Helenius-Hietala et al, 2012), (Ladegaard Grønkjaer et al, 2021), (Lins et al, 2011), (Pidhorodeckyj et al, 2018), (Ramaglia et al, 2019).…”
Section: Em Relação a Condição Oralunclassified
See 2 more Smart Citations
“…In an observational study of liver cirrhosis patients, poor oral health correlated with the progression of liver cirrhosis during the year preceding the dental examination [ 96 ]. Other researchers reported that periapical radiolucency as a sign of periapical inflammation was associated with the prevalence of cirrhosis-related complications such as ascites, hepatic encephalopathy and/or variceal bleeding [ 97 ], and the presence of dental calculus predicted worse survival among liver transplant candidates [ 98 ]. Furthermore, Bajaj et al found higher endotoxin levels in saliva of cirrhosis patients compared to healthy controls [ 99 ], and salivary dysbiosis predicted incident cirrhosis decompensation events [ 99 ].…”
Section: Oral-gut-liver Axismentioning
confidence: 99%